Aktivitas Manajemen Pendidikan Islam dalam Pemberdayaan Perempuan melalui Pendidikan Nonformal di Kota Medan - Sifa Maulida; Amiruddin Siahaan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the role of Islamic education management in women's empowerment through non-formal education in Medan City, focusing on the programs of the Women, Youth, and Family Commission (KPRK) of the Indonesian Ulama Council (MUI). Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving KPRK leaders and training participants. The results indicate that KPRK MUI Medan implements Islamic education management principles—planning, organizing, actuating, and evaluating—in its non-formal education programs, such as the Female Ulama Cadre Education (PKU-P). These programs enhance women's religious literacy, leadership skills, and social participation, aligning with Islamic values of ta'dib (moral development) and tarbiyah (holistic education). The study concludes that non-formal education is an effective strategy for empowering women in religious and social contexts, addressing structural and cultural barriers.